KOMPARASI PEMBERIAN KOMPRES AIR JAHE MERAH HANGAT DAN KOMPRES AIR JAHE PUTIH HANGAT TERHADAP NYERI PUNGGUNG PADA IBU HAMIL TRIMESTER III DI PUSKESMAS RAWASARI KOTA JAMBI - Astiandah Elsanes; Sri Mulyani; Meinarisa; Muthia Mutmainnah; Rina Oktaria (Jurnal Multidisipliner Kapalamada, 2025)
This study aims to examine the comparison between warm red ginger compresses and warm white ginger compresses on back pain in third-trimester pregnant women at Rawasari Health Center, Jambi City. This research is a quantitative study with a quasi-experimental design: equivalent two-group pretest-posttest design. The sample consisted of 34 third-trimester pregnant women divided into two groups (17 red ginger, 17 white ginger) using consecutive sampling technique. Data analysis was performed using the Wilcoxon test and the Mann-Whitney test. The results showed differences in the changes in back pain levels between the two intervention groups, with a greater reduction in back pain observed in pregnant women who received warm red ginger compresses. Therefore, non-pharmacological therapy in the form of warm red ginger compresses can be recommended to healthcare professionals as an effort to reduce back pain in women during the third trimester of pregnancy.